2013
DOI: 10.1186/1479-5868-10-78
|View full text |Cite
|
Sign up to set email alerts
|

Walking for transportation in Hong Kong Chinese urban elders: a cross-sectional study on what destinations matter and when

Abstract: BackgroundWalking for transport can contribute to the accrual of health-enhancing levels of physical activity in elders. Identifying destinations and environmental conditions that facilitate this type of walking has public health significance. However, most findings are limited to Western, low-density locations, while a larger proportion of the global population resides in ultra-dense Asian metropolises. We investigated relationships of within-neighborhood objectively-measured destination categories and enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
108
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(124 citation statements)
references
References 24 publications
10
108
4
2
Order By: Relevance
“…This suggests that given the opportunity to travel to destinations of interest nearby, older adults may be willing to walk instead of drive to reach them. Two recent studies have found that the presence of destinations, measured in terms of destination diversity (Cerin et al, 2013;Rosso et al, 2013) and prevalence (Cerin et al, 2013), is associated with the within-neighborhood mobility of older adults. These analyses, like our multivariable analysis using Street Smart Walk Score, rely on composite indices of walkability categories that were not tailored to older adult populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that given the opportunity to travel to destinations of interest nearby, older adults may be willing to walk instead of drive to reach them. Two recent studies have found that the presence of destinations, measured in terms of destination diversity (Cerin et al, 2013;Rosso et al, 2013) and prevalence (Cerin et al, 2013), is associated with the within-neighborhood mobility of older adults. These analyses, like our multivariable analysis using Street Smart Walk Score, rely on composite indices of walkability categories that were not tailored to older adult populations.…”
Section: Discussionmentioning
confidence: 99%
“…Further, living in neighborhoods that are close to destinations may provide the opportunity for older adults to walk, instead of drive, and thereby obtain incidental physical activity. Some studies have found a positive association between the presence and proximity of various types of destinations and older adults' walking (Cao et al, 2010;Gauvin et al, 2012;Michael et al, 2006Michael et al, , 2010Nagel et al, 2008;Nathan et al, 2012), walking for transport (Cao et al, 2010;Cerin et al, 2013;King, 2008), and physical activity (Cao et al, 2010;Cerin et al, 2013;King, 2008). However, findings regarding the specific types of destinations associated with walking are not consistent.…”
Section: Introductionmentioning
confidence: 99%
“…The following data for the characterization of built environment attributes come from Zhongshan Municipal Bureau of Urban Planning (Zhang et al, 2013;Zhang et al, 2014a): (1) traffic analysis zones' boundaries-proxy for neighborhood boundaries; (2) land use in 2010 with five major types of land use (residential land, commercial and service facilities, industrial and manufacturing, green space, and other types); (3) neighborhood population in 2010; (4) road networks; (5) bus stops; and (6) political boundaries, such as city and zone boundaries. All the data were then integrated into ArcGIS for further analysis.…”
Section: Data Collectionmentioning
confidence: 99%
“…Benefits of engaging in exercises are well known [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Exercising regularly can help increasing the total sleeping time and depth of sleep, as well as decreasing sleep onset latency [52].…”
Section: Introductionmentioning
confidence: 99%